Dampak Pengembangan Pariwisata MICE terhadap Ekonomi, Sosial, dan Budaya Masyarakat Lokal di Kawasan Nusa Dua Bali - Rahjasa, Putu Surya Laksana (Green Publisher Indonesia, 2025)
This study aims to analyze the impact of MICE (Meetings, Incentives, Conferences, and Exhibitions) tourism development on the economic, social, and cultural aspects of local communities in the Nusa Dua area of Bali and its surrounding regions, including Tanjung Benoa and Jimbaran. Using a literature review method and a descriptive qualitative approach, the study gathers secondary data from scholarly articles, institutional reports, and official publications. The findings indicate that MICE tourism significantly contributes to economic growth through increased hotel occupancy, job creation, and the strengthening of supporting sectors such as SMEs and professional services. Socially, MICE activities enhance community skills development but also cause disparities in access and strain local infrastructure. Culturally, while MICE events promote local heritage and serve as a means of cultural diplomacy, they also risk commodifying culture if not accompanied by authentic preservation efforts. The study recommends participatory policies that balance economic growth with the sustainability of the local social and cultural fabric.